Quantitation of Human Platelet Transformation on Siliconized Glass: Comparison of “Normal” and “Abnormal” Platelets - Rosenstein, R; Zacharski, L R; Allen, R D (Thrombosis and Haemostasis, 1981)
A series of typical morphological stages, representing progression of transformation, may be defined following adhesion of platelets to a siliconized glass surface. Platelets are visualized by new light microscopic techniques that allow quantitative categorization of transformation of large platelet populations by morphological stage, and thus the detection and elucidation of platelet defects which influence transformation. Living platelets from each of five subjects with bleeding disorders, due to platelet defects, exhibited a pattern of morphologic transformation which differed from normal. In addition, the pattern observed with the platelets from a subject with Glanzmann’s thrombasthenia was sufficiently different from that observed with the platelets from four subjects with thrombopathy, so as to point to a qualitative difference in the activity of the platelets in the two disorders. These findings indicate that the analysis of platelet transformation in vitro through the use of light microscopy may allow for detection and further classification of platelet abnormalities.
Keywords: Light microscopy; Platelet adhesion and transformation; Glanzmann’s thrombasthenia; Storage pool disease; Thrombopathy